A beam-bending eigenstrain analysis of residual elastic strains in multi-scan laser-formed steel samples - Korsunsky, A; Vorster, W; Zhang, S; Topić, M; Venter, A (Professional Engineering Publishing, 2008)
Laser-induced forming and microstructural modification of materials and components is a technique that offers interesting possibilities for improved control over the final state of the workpiece, and the possibility of generating carefully tailored residual stress states and spatially varying microstructures best suited to specific industrial applications. A key challenge in the development of this technique is the characterization of the relationship between process parameters and the resulting state of the workpiece; and the optimization of processing conditions in order to deliver a desired result. The results of an experimental study of microstructure and residual elastic strains (RES) in multi-scan laser-bent steel plates by the combination of microscopy and strain mapping using energy-dispersive synchrotron X-ray diffraction have been recently reported. This paper is devoted to the presentation of simplified eigenstrain analysis of the RES fields arising due to laser processing that allows approximate plastic strain profiles to be extracted for the purpose of improved process characterization and optimization.